Pager Mangkok Luwih Bakuh Tinimbang Pager Tembok: Negasi Sekuritas dalam Falsafah Jawa - Fibiona, Indra; Lestari, Siska Nurazizah (Mahesa Research Center (PT. Mahesa Global Publishing), 2022)
Javanese community has a philosophy of